The development and evaluation of a design thinking module to facilitate creativity among lower secondary school students / Adila Md Hashim - Md Hashim, Adila (2023)
This study focuses on developing a design thinking module to facilitate creativity among lower secondary school students. The module development is to overcome students' lack of creativity in creating solutions to real-world problems. The study adopted the Design and Development Research in three phases: needs analysis, design and development, and evaluation. A structured interview was used with nine lower secondary school teachers in phase one to identify the needs to develop the module. Content analysis was utilised to determine the relevant themes. As mentioned by the teachers, there is a lack of creativity among lower secondary school students. They also mentioned that design thinking can facilitate students' creativity and agreed that a design thinking module is needed to guide students in executing design thinking in schools. During the second phase, a semi-structured interview based on phenomenology was conducted face-to-face with four design-thinking practitioners. The interview transcripts were analysed using thematic analysis to decide the content of the module. It was further selected using the design thinking content selection instrument by eight teachers experienced in implementing design thinking in schools. The data was then analysed using the Fuzzy Delphi method to determine experts' consensus on suitable content for lower secondary school students. Once the design thinking module was developed, the four stages of Tessmer formative evaluation were performed to measure and improve its usability. The first stage was conducted with two creativity experts via email. The second stage was conducted face-to-face with two teachers and two students. The third and fourth stages were implemented at a secondary school with eight and thirty-two lower secondary school students, respectively. They used the module to apply design thinking in an actual environment. It was found that the usability of the design thinking module was first rated at 3.76, followed by 3.63 in stage two and 4.43 in stage three. The final usability of the design thinking module was rated at 4.27, indicating good. Meanwhile, students' creativity was assessed based on three indicators; think creatively, work creatively with others and implement innovations. The data retrieved during the formative evaluation's third and fourth stages were based on creativity observation while students executed design challenges. Based on the findings, it can be concluded that the design thinking module can facilitate lower secondary school students' creativity and be used as a guide in executing the design thinking approach in schools with close supervision of teachers.